PENERAPAN KONSEP LEAN MANUFACTURING UNTUK MENDESAIN ULANG TATA LETAK FASILITAS DI INDUSTRI USAHA MIKRO KECIL MENENGAH - Setia Teguh Wirawan; Adelina Suryati (Gapenas Publisher, 2023)
The aims of this study were to redesign the production floor layout with lean manufacturing in mind to eliminate waste and use the Block Layout Overview with Layout Planning (BLOCPLAN) algorithm to achieve a new facility layout in the Indonesian home food industry. One solution to address this problem is to improve work areas (work stations) on the production floor by rearranging and designing standard operating procedures (SOPs) using the concept of lean manufacturing. The new layout can reduce the loss from the actual condition. Practical implications This research is beneficial for small and medium enterprises (MSMEs) in Indonesia, especially the home food industry. The BLOCPLAN layout (as a recommendation) has a displacement moment with a 40 percent reduction. Production facility layout design is a method used to rearrange the production process area so that the distance between processes can be minimized. SOP is given as direction and supervision of workers to work according to standards. Originality/SOP design value can support the recommended layout as a reference in making cakes (products) to eliminate waste, namely movement (alternating production process flow) and length.